2021
DOI: 10.3390/coatings11070791
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Coatings for Orthopedic Metallic Implants

Abstract: Titanium, stainless steel, and CoCrMo alloys are the most widely used biomaterials for orthopedic applications. The most common causes of orthopedic implant failure after implantation are infections, inflammatory response, least corrosion resistance, mismatch in elastic modulus, stress shielding, and excessive wear. To address the problems associated with implant materials, different modifications related to design, materials, and surface have been developed. Among the different methods, coating is an effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 150 publications
(89 reference statements)
1
31
0
Order By: Relevance
“…As metallic biomaterials represent key elements for hard tissue replacement and restoration, a plethora of efforts have been undertaken to limit their main shortcomings, namely bioinertness and poor bioactivity. Many studies confirmed the importance of surface characteristics for reaching a proper and augmented osseointegration [10][11][12][13], with a special emphasis forming a bioactive implant-to-bone interface.…”
Section: Introductionmentioning
confidence: 90%
“…As metallic biomaterials represent key elements for hard tissue replacement and restoration, a plethora of efforts have been undertaken to limit their main shortcomings, namely bioinertness and poor bioactivity. Many studies confirmed the importance of surface characteristics for reaching a proper and augmented osseointegration [10][11][12][13], with a special emphasis forming a bioactive implant-to-bone interface.…”
Section: Introductionmentioning
confidence: 90%
“…These can be either nitinol-based and composites thereof [ 151 , 152 ] or more unusual coating materials such as hardystonite [ 153 ]. Some examples of such coatings were recently reviewed by Hussain et al [ 154 ].…”
Section: Coating Materials Selectionmentioning
confidence: 99%
“…Conventional materials suggested as coatings on titanium for enhanced biocompatibility include hydroxyapatite, bioactive glass, biphasic calcium phosphate and TiN. However, the stability, adhesion, and degradation performance of these coatings are still challenging [4,5]. The drawbacks and limited performance can be partly attributed to the quality and coverage of coatings which has a direct effect on responses such as initial cellular adhesion to a substrate, subsequent growth and proliferation, and bioactivity of material [6].…”
Section: Introductionmentioning
confidence: 99%